El Excentrico, 1976-01-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, CA, 2024)
January 5, 1976 [5 de enero de 1976]. Ano 26, No 19. Cover has an illustraion of a couple in formal attire. This illustration was advertising the Imperial Valley California Club Anniversary Dance, which would take place on February 7th, 1976 in the Fiesta Hall on the Santa Clara County Fairgrounds.